2023
DOI: 10.1186/s40359-023-01074-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with anxiety and depression in patients with erectile dysfunction: a cross-sectional study

Abstract: Background Few studies have investigated factors associated with anxiety and depression among patients with erectile dysfunction (ED). This study aimed to investigate associated factors and the prevalence of anxiety and depression in this special group in China. Methods Data from 511 patients with ED aged 18–60 years were collected between July 2021 and April 2022. The 5-item International Index of Erectile Function (IIEF-5) questionnaire, self-rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Accordingly, sexual dysfunctions could lead to anxious status, which can increase the likelihood of future sexual failure, creating a vicious circle. 38 Consequently, it is not surprising that in our analysis men presenting with concomitant ED and uOD, with respect to ED-only patients, more frequently reported anxiety and had higher rates of depressive symptoms and lower scores in all IIEF domains, thus indicating the potential disruption of the overall sexual response cycle. 1 This emerges to be of particular importance in the clinical practice because the combination of embarrassment and mood deflection leaves men even more fragile, with different expectations and probably less prone to follow further physicians' suggestions.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Accordingly, sexual dysfunctions could lead to anxious status, which can increase the likelihood of future sexual failure, creating a vicious circle. 38 Consequently, it is not surprising that in our analysis men presenting with concomitant ED and uOD, with respect to ED-only patients, more frequently reported anxiety and had higher rates of depressive symptoms and lower scores in all IIEF domains, thus indicating the potential disruption of the overall sexual response cycle. 1 This emerges to be of particular importance in the clinical practice because the combination of embarrassment and mood deflection leaves men even more fragile, with different expectations and probably less prone to follow further physicians' suggestions.…”
Section: Discussionmentioning
confidence: 72%
“…Trovão and Serefoglu 36 showed that OD in depressed men could be a consequence of a disrupted desire and/or arousal phase; once sexual arousal is impeded, orgasm and ejaculation will not be initiated. Accordingly, sexual dysfunctions could lead to anxious status, which can increase the likelihood of future sexual failure, creating a vicious circle 38 . Consequently, it is not surprising that in our analysis men presenting with concomitant ED and uOD, with respect to ED‐only patients, more frequently reported anxiety and had higher rates of depressive symptoms and lower scores in all IIEF domains, thus indicating the potential disruption of the overall sexual response cycle 1 .…”
Section: Discussionmentioning
confidence: 80%
“… 46 However, reverse causality could also exist; that is, ED can cause mental health symptoms and vice versa. 47 In a systematic review, Liu et al estimated that men with depression had a 2.92-times higher probability of experiencing ED (odds ratio, 2.92; 95% CI, 2.37-3.60). 48 In Chinese men aged 22 to 50 years, Zhang et al found a higher proportion of ED in those with depressive and anxious symptoms ( P = .002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sexual dysfunction itself can affect mental health [112]. and administer individualized treatment in a timely manner [113].…”
Section: Psychiatric Disordersmentioning
confidence: 99%